KÓPJAQLÍLAR KESIMLERIN JASAWDA GEOGEBRA BAǴDARLAMASÍNAN PAYDALANÍW JOLLARÍ - Qaypnazarova, G.X.; Kudenov, T.M. (SCIENCE and SOCIETY, 2021)
The article discusses the use of the Geogebra program in geometry lessons on the topic of cross-sections of polyhedra. Brief information about the Geogebra program is given. The drawings in the conditions of the problem were drawn for using for Geogebra program. The relevance and practical significance of the research topic is indicated.